RASIO SEKS JERNANG (Daemonorops draco (Willd.)Blume) PADA POPULASI ALAMI DAN BUDIDAYA: IMPLIKASI UNTUK PRODUKSI BIJI - Asra, Revis; Syamsuardi, Syamsuardi; Mansyurdin, Mansyurdin; Ridho Witono, Joko (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2012)
Jernang (Daemonorops draco (Willd.) Blume) is a dioecious rattan species that produces resin on female individuals. The sex of jernang can only be identified from its inflorescences morphology. Sex survey was conducted in 5 populations ofÂ jernang, 3 populations of which in the Bukit Tigapuluh National Park (BTNP), 1 population in the secondary forest in Jambi province and 1 population in the area of rubber plantation in Jambi province. Chi-Squared test on the sex ratio ofÂ jernang showed that the ratio of the male to female in their natural habitat (Bengayoan and Tebo, 2 parts of the BTNP ecosystem and the Sepintun secondary forest) was distorted from the normal ratio of 1:1, while the cultivated jernang in Nunusan population (BTNPT) and Mandiangin were not significantly different from the normal sex ratio of 1:1. Female individuals from the cultivated population in the Mandiangin (planted in 1997) has an average number of stems per clump more on individual males (27.12) than females (26.92). The result of this study indicated that the D. draco has a good reproductive strategy and thus suitable for cultivation.